Do obstetricians apply the national guidelines? A vignette‐based study assessing practices for the prevention of preterm birth. (29th December 2019) - Rousseau, A; Azria, E; Baumann, S; Deneux‐Tharaux, C; Senat, MV
Abstract : Objective: To describe spontaneous preterm birth prevention practices self‐reported before and after the dissemination of relevant guidelines, and to identify personal and organisational factors associated with adherence. Design: A repeated cross‐sectional vignette‐based survey study. Setting: French obstetricians. Population: French obstetricians practicing in public or private maternity units. Methods: Before and after the dissemination of the 2017 French guidelines on the prevention of spontaneous preterm birth, participants were asked to complete a web‐based self‐administered questionnaire based on two clinical vignettes. Vignette 1 focused on respondents' attitudes towards strict bed rest, cerclage, and progesterone treatment for women with a short cervix in mid‐trimester; vignette 2 focused on attitudes towards strict bed rest and maintenance tocolysis after successful tocolysis for preterm labour. A mixed quantitative and qualitative analysis was conducted. Main outcome measures: Non‐adherence to guidelines for the prevention of spontaneous preterm birth in responses to each vignette. Results: We obtained complete responses from 286 obstetricians before and 282 obstetricians after guideline dissemination, including 145 obstetricians participating in both. After dissemination, 51.4% of obstetricians self‐reported non‐adherent practices for vignette 1 and 22.3% of obstetricians self‐reported non‐adherent practices for vignette 2. No improvement was observed after dissemination. The quantitative analysis identified factors associated with non‐adherence, including older age and practice in non‐university or small hospitals, whereas the qualitative analysis highlighted barriers to implementation, including fear of change, habits, work overload, and lack of time. Conclusions: Adherence to guidelines was generally low, with practices unmodified by their dissemination. Improvement is required, especially regarding applicability. Tweetable abstract: Adherence to guidelines to prevent spontaneous preterm birth was generally low and remained unmodified after guideline dissemination. Tweetable abstract: Adherence to guidelines to prevent spontaneous preterm birth was generally low and remained unmodified after guideline dissemination.